CURRENT ROLE OF SOCIAL MEDIA IN AESTHETIC PLASTIC SURGERY: WHY PLASTIC SURGEONS MUST TAKE CONCERN? - Amandita, Tiara Amanna; Saraswati, Hastika (Universitas Airlangga, 2023)
Highlights: This study shows that in the era of society 5.0, digital technology has played a major role in doctor-patient communication in the medical field, especially in plastic aesthetic surgery. Only a few plastic surgeons comprehend this digital transformation. It is hoped that this study will help plastic surgeons better understand and adapt to social media. Abstract: Introduction: In the medical field, particularly in areas like plastic aesthetic surgery and cosmetology, social media has emerged as a convenient and interactive means of educating and promoting the services of doctors, hospitals, and institutions. However, there remains a pressing need for further research to thoroughly understand the influence of social media on plastic surgery procedures. This study aims to review the literature on the current facets of social media that impact patients' decision-makingin aesthetic plastic surgery. Methods: Database PubMed was used for the search terms: